1997
DOI: 10.1074/jbc.272.49.30945
|View full text |Cite
|
Sign up to set email alerts
|

A Selective ε-Protein Kinase C Antagonist Inhibits Protection of Cardiac Myocytes from Hypoxia-induced Cell Death

Abstract: Protein kinase C activation is thought to protect cardiac tissue from subsequent ischemic injury by a process termed preconditioning. The protein kinase C isozyme that mediates preconditioning has not yet been identified. Using a cell culture model of hypoxic preconditioning, we found that cardiac myocyte viability after 9 h of hypoxia was increased by more than 50% over control. Preconditioning activated protein kinase C isozymes as evidenced by translocation from one cell compartment to another as follows: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
307
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 369 publications
(326 citation statements)
references
References 41 publications
17
307
0
Order By: Relevance
“…As expected (2,13,28,35,38), subjecting cultured cardiomyocytes to an episode of sublethal hypoxia decreased cell death induced by subsequent simulated lethal ischemiareperfusion, as measured by the MTS and LDH assays (Fig. 1).…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…As expected (2,13,28,35,38), subjecting cultured cardiomyocytes to an episode of sublethal hypoxia decreased cell death induced by subsequent simulated lethal ischemiareperfusion, as measured by the MTS and LDH assays (Fig. 1).…”
Section: Resultsmentioning
confidence: 76%
“…We also measured the cellular protein levels of HIF-1␣ and the mRNA levels of several HIF-1 target genes in a cultured neonatal rat cardiomyocyte model of preconditioning (2,13,23,28,35,38). Our results suggest that expression of a constitutively stable hybrid HIF-1␣ protects cultured neonatal cardiomyocytes against simulated ischemia-reperfusion injury by inducing multiple protective genes.…”
mentioning
confidence: 96%
“…Once the peptide crosses the cell membrane, the disulfide bond breaks, the peptide cargo is trapped in the cell, and the peptide carrier can be washed out. These studies already demonstrated that the peptides have highly selective effects; they inhibit or induce translocation of their corresponding isozymes but not that of others (Gray et al, 1997;Dorn et al, 1999). In addition, at concentrations up to ϳ10 M, the peptides or the carrier have no toxic effects on the cell.…”
Section: Peptide Preparation and Deliverymentioning
confidence: 94%
“…The ⑀V1-2 [⑀PKC inhibitor, amino acids 14 -21 (EAVSLKPT)] (Gray et al, 1997) and ⑀RACK [⑀PKC activator, amino acids 85-92 (HDAPI-GYD)] (Dorn et al, 1999) peptides were synthesized at Stanford's Protein and Nucleic Acid facility and conjugated to Tat [carrier peptide, amino acids 47-57 (YGRKKRRQRRR)] (Schwarze et al, 1999) via a cysteine-cysteine bond at their N termini, as described previously (Chen et al, 2001).…”
Section: Peptide Preparation and Deliverymentioning
confidence: 99%
“…Cardiac preconditioning, which has been demonstrated in many species, can be induced through a variety of methods including hypoxia/ischemia [40], anesthetics [41], glucose [42], phorbol esters [43], cannabinoids [44], and heat-stress [45]. It is assumed that these act in a unified manner and activation of PKCε is, most likely, key to this control [46].…”
Section: Two Pkcs Which Respond To Stress Pkcε In the Heartmentioning
confidence: 99%